Sodium-ion battery electrolyte containing NaSO3F and sodium-ion battery

By using NaSO3F as the electrolyte salt in sodium ion battery electrolyte, combined with ester solvents and film-forming additives, the problems of high cost, poor safety and poor electrochemical performance of the electrolyte salt are solved, and a low-cost and high-performance electrolyte solution is achieved, with excellent thermal stability and compatibility.

CN119674186APending Publication Date: 2025-03-21WUHAN FLULAIMEI NEW ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411992296.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The electrolyte salts in existing sodium ion battery electrolytes have problems such as high cost, poor safety and poor electrochemical performance.

Method used

NaSO3F is used as the electrolyte salt, combined with ester solvents and film-forming additives, and a low-cost and high-performance sodium ion battery electrolyte is prepared, and sodium difluoroxalic acid borate is introduced into the electrolyte to improve compatibility.

Benefits of technology

The electrochemical performance similar to that of NaClO4 and NaPF6 is achieved, which avoids the potential for deflagration, has excellent thermal stability and wide electrochemical window, and is suitable for both Na metal anode and hard carbon anode, with excellent capacity retention and Coulomb efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674186A_ABST
    Figure CN119674186A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of sodium ion batteries, and particularly relates to a sodium ion battery electrolyte containing NaSO3F and a sodium ion battery. According to the sodium ion battery electrolyte provided by the invention, the electrolyte salt contains NaSO3F, experiments find that a battery assembled by the NaSO3F-based electrolyte has excellent cycle capacity retention rate and coulombic efficiency, the capacity retention rate of the NaSO3F-based electrolyte still reaches 99% or above after 100 cycles, and the coulombic efficiency also reaches 99% or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of sodium ion batteries, and more specifically, to a sodium ion battery electrolyte containing NaSO3F and a sodium ion battery. Background Art

[0002] The electrolyte of a sodium battery is generally composed of three parts: an organic solvent, an electrolyte salt, and necessary additives. It plays the role of conducting ions between the positive and negative electrodes of the battery and is a very important part of the battery. In addition, the cost of the battery is a key factor in determining whether it can be used in practice, especially in the field of large-scale energy storage applications, where cost becomes the top priority. Studies have shown that the cost of the electrolyte accounts for about 10% to 15% of the entire power battery production. Among them, the electrolyte accounts for 50% of the electrolyte cost. Therefore, in order to promote the industrialization of sodium-ion batteries, a low-cost, high-performance electrolyte system is needed.

[0003] At present, the commonly used electrolyte salts are NaClO4, NaPF6, NaFSI, NaTFSI, NaOTf, etc. NaPF6 is the most commonly used sodium salt in sodium batteries and is also the electrolyte salt with the highest comprehensive performance. However, its synthesis process requires two or more steps of reaction and involves corrosive gases such as PF5 and HF. A lower condensation temperature is required during the purification process. These properties will increase the use and maintenance costs of production equipment.

[0004] Sodium perchlorate (NaClO4) is the most commonly used sodium salt in the laboratory and has the longest research history. After dissolving, NaClO4 has high conductivity, low cost, and low sensitivity to moisture. The anion has strong antioxidant capacity and is suitable for high-voltage electrolyte systems. It has good compatibility with carbon-based negative electrodes and produces a low SEI membrane interface impedance. However, the serious problem with sodium perchlorate is that because the chlorine element is in the highest oxidation state, it is highly oxidizing and poses a safety hazard. Summary of the invention

[0005] In view of the defects of the prior art, the purpose of the present application is to provide a sodium ion battery electrolyte and a sodium ion battery containing NaSO3F, aiming to solve the problems of high cost, poor safety and poor electrochemical performance of electrolyte salts in the prior art sodium ion battery electrolyte.

[0006] To achieve the above objectives, in a first aspect, the present application provides a sodium ion battery electrolyte containing NaSO3F, comprising an electrolyte salt, a solvent and an additive, wherein the electrolyte salt contains NaSO3F.

[0007] Preferably, the solvent is an ester solvent.

[0008] Further preferably, the solvent is one or more of ethylene carbonate, propylene carbonate, dimethyl ether, diethyl carbonate and THF.

[0009] Preferably, the concentration of NaSO3F in the electrolyte is 0.5-2M.

[0010] Preferably, the additive is a film-forming additive, more preferably fluoroethylene carbonate and / or vinylene carbonate.

[0011] Preferably, the volume percentage of the additive in the electrolyte is less than or equal to 5%.

[0012] Preferably, the electrolyte salt further contains sodium difluorooxalatoborate; preferably, the molar ratio of NaSO3F to sodium difluorooxalatoborate in the electrolyte salt is less than or equal to 1:1.

[0013] According to another aspect of the present invention, there is provided a sodium ion battery comprising the electrolyte.

[0014] Preferably, the electrolyte salt in the electrolyte is NaSO3F, and the sodium ion battery further comprises a positive electrode and a negative electrode, the positive electrode is polyacrylonitrile-sulfur, and the negative electrode is a Na metal negative electrode or a hard carbon negative electrode.

[0015] Further preferably, the electrolyte contains NaSO3F and sodium difluorooxalatoborate at the same time; the sodium ion battery also includes a positive electrode and a negative electrode, the positive electrode is sodium vanadium phosphate, sodium nickel iron manganese oxide, Prussian blue or polyacrylonitrile-sulfur, and the negative electrode is a Na metal negative electrode or a hard carbon negative electrode.

[0016] In general, the above technical solutions conceived by this application have the following beneficial effects compared with the prior art:

[0017] (1) The present invention provides a sodium ion battery electrolyte, wherein the electrolyte salt contains NaSO3F. Experiments have shown that the electrochemical performance of the sodium ion battery prepared by using NaSO3F as the electrolyte salt of the sodium ion battery is comparable to that of the commonly used electrolyte salts NaClO4 and NaPF6. In addition, the NaSO3F-based electrolyte does not have the risk of explosion of the NaClO4-based electrolyte, and its thermal stability is better than that of NaPF6, and it will only decompose at a temperature above 425°C. The conductivity of 1M NaSO3F in PC solvent can reach 4.4mS / cm, which meets the conductivity requirements of conventional sodium battery electrolytes.

[0018] (2) The electrochemical window of the NaSO3F electrolyte of the present invention is relatively wide. Regarding oxidation stability, the oxidation voltage of the three electrolytes is ranked from high to low as follows: NaClO4>NaSO3F>NaPF6. The oxidation potential of the NaSO3F electrolyte is about 4.2V (vs.Na / Na+ ).

[0019] (3) The present invention uses NaSO3F as the electrolyte salt in the sodium ion battery electrolyte. After assembling the battery, it is found that the electrolyte is applicable to both Na metal negative electrodes and hard carbon HC negative electrodes, and has better matching with HC negative electrodes, and has excellent capacity retention and coulombic efficiency. Its first charge and discharge efficiency is 85.32%, which is similar to the first efficiency of the NaPF6 group. After 100 cycles, the capacity retention rate of the NaSO3F group still reaches more than 99%, and the coulombic efficiency also reaches more than 99%, while the capacity retention rate of the NaPF6 group after 100 cycles is only 86%.

[0020] (4) The experiment found that when the electrolyte of the present invention, NaSO3F, is used as the only electrolyte salt, and matches three conventional sodium ion battery positive electrode materials, namely sodium vanadium phosphate, sodium nickel iron manganese oxide, and Prussian blue, the battery has a slight internal short circuit phenomenon, resulting in the battery charging voltage failing to reach the theoretical expectation and failing to discharge effectively. At this time, it can only match the S@pPAN positive electrode material. However, after further introducing sodium difluorooxalatoborate into the electrolyte, the short circuit phenomenon disappears, and it can well match sodium vanadium phosphate, sodium nickel iron manganese oxide, Prussian blue, and S@pPAN positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the crystal structure of NaSO3F, where S-yellow, O-red, Na-purple, and F-green;

[0022] Figure 2 The S@pPAN||Na battery was assembled with NaSO3F, NaPF6, and NaClO4 as electrolyte salts and PC as solvent, and 5% (volume ratio) FEC was added. The cycle number-charge capacity-coulomb efficiency diagram at a rate of 0.1C (1C = 1650 mAh / g) was plotted, and the charge and discharge range was 0.7V to 3.0V.

[0023] Figure 3 NaSO3F and NaPF6 are electrolyte salts, EC:PC (1:1) is solvent, and Na||HC battery is assembled with 2% FEC, and the rate is 0.1C (1C = 300mAh / g), wherein (a) EIS graph before cycle, bias voltage is 30mV; (b) cycle number-discharge specific capacity-coulombic efficiency graph;

[0024] Figure 4The S@pPAN||Na battery was assembled with NaSO3F as electrolyte salt, PC as solvent, 5% FEC and 5% VC added, and the rate was 0.1C (1C = 1650 mAh / g). The comparison chart of cycle number-charge capacity-coulombic efficiency is in the charge and discharge range of 0.7V to 3.0V.

[0025] Figure 5 Comparison of the charge and discharge curves of the battery at the 1st, 50th and 250th cycles with NaSO3F as the electrolyte salt, PC as the solvent, and 5% FEC and 5% VC added. The charge and discharge range is 0.7V to 3.0V.

[0026] Figure 6 S@pPAN||Na batteries were assembled with NaSO3F as electrolyte salt, PC as solvent, 5% FEC and 5% VC added, and their rate performance was tested. The rates were 0.05C, 0.1C, 0.25C, 0.5C, 1C, 3C, 0.1C (1C = 1650mAh / g), and the charge and discharge range was 0.7V to 3.0V.

[0027] Figure 7 The time-voltage curve (content (a)) and capacity-voltage curve (content (b)) of the battery charge-discharge cycle of a battery with sodium nickel iron manganese oxide as the positive electrode, Na as the negative electrode, 1M NaSO3F as the electrolyte, and a rate of 0.1C (1C = 300mAh / g);

[0028] Figure 8 The time-voltage curve of a battery with Na as the negative electrode, 1M NaSO3F as the electrolyte, and a rate of 0.1C; (a) sodium vanadium phosphate as the positive electrode; (b) Prussian blue as the positive electrode. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0030] The embodiments of the present invention are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and processes are given, but the protection scope of the present invention is not limited to the following embodiments. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.

[0031] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0032] The process parameters without specific conditions in the following examples are usually based on conventional conditions.

[0033] The invention provides a sodium ion battery electrolyte containing NaSO3F, comprising an electrolyte salt, a solvent and an additive, wherein the electrolyte salt contains NaSO3F.

[0034] In some embodiments, the solvent is an ester solvent. Preferably, the solvent is one or more of EC (ethylene carbonate), PC (propylene carbonate), DME (dimethyl ether), DEC (diethyl carbonate) and THF.

[0035] In some embodiments, the concentration of NaSO3F in the electrolyte is 0.5-2M.

[0036] In some embodiments, the additive is a film-forming additive, preferably FEC (fluoroethylene carbonate) and / or VC (vinylene carbonate). The volume percentage of the additive in the electrolyte is less than or equal to 5%.

[0037] In a preferred embodiment, the electrolyte salt further contains sodium difluorooxalatoborate; more preferably, the molar ratio of NaSO3F to sodium difluorooxalatoborate in the electrolyte salt is less than or equal to 1:1.

[0038] It was found in the experiment that when NaSO3F is used as the only electrolyte salt in the electrolyte, the positive electrode material that can be adapted is sulfur-based polyacrylonitrile positive electrode material, or polyacrylonitrile-sulfur, abbreviated as S@pPAN. However, if sodium vanadium phosphate, sodium nickel iron manganese oxide, or Prussian blue is used as the positive electrode material, a short circuit will occur. Therefore, the sodium ion battery provided by the present invention is preferably a room temperature sodium-sulfur battery, comprising an electrolyte, and the electrolyte salt in the electrolyte is NaSO3F, and also comprising a positive electrode and a negative electrode, the positive electrode is a sulfur-based polyacrylonitrile positive electrode material, abbreviated as S@pPAN, and the negative electrode is Na or a hard carbon negative electrode, abbreviated as HC. However, when sodium difluorooxalatoborate is further introduced into the electrolyte salt of the present invention, and the molar ratio of NaSO3F to sodium difluorooxalatoborate is less than or equal to 1:1, the electrolyte can well match a variety of positive electrode materials including sodium vanadium phosphate, sodium nickel iron manganese oxide, Prussian blue and sulfur-based polyacrylonitrile positive electrode material S@pPAN. Therefore, the present invention also provides a battery, preferably a room temperature sodium-sulfur battery, comprising an electrolyte, the electrolyte containing two electrolyte salts, NaSO3F and sodium difluorooxalatoborate, and also comprising a positive electrode and a negative electrode, the positive electrode is sodium vanadium phosphate, sodium nickel iron manganese oxide, Prussian blue or sulfur-based polyacrylonitrile positive electrode material S@pPAN, and the negative electrode is Na or a hard carbon negative electrode HC.

[0039] The present invention proposes to use sodium salt NaSO3F as an electrolyte salt in a battery. The crystal structure of NaSO3F is as follows Figure 1 It is inferred that in the NaSO3F structure, due to the strong electronegativity of fluorine and oxygen, the negative charge of sulfur can be dispersed. Therefore, NaSO3F has anions dispersed in four directions and carries a negative charge. This structure makes the anions and Na + The binding energy between them becomes smaller, which is beneficial to improving the conductivity of NaSO3F-based electrolyte. In addition, its structure contains SF bonds, which is beneficial to the formation of a better interface film during the battery cycle. NaSO3F has excellent thermal stability and no risk of deflagration. The present invention uses NaSO3F as an electrolyte salt in a room temperature sodium-sulfur battery. In the preferred embodiment, the positive electrode is selected as the S@pPAN positive electrode. When 5% VC is added, the cycle performance of the S@pPAN||Na battery is even better than that of NaPF6. In addition, the NaSO3F-based electrolyte is also very stable to the HC negative electrode.

[0040] The electrolyte salt NaSO3F used in the embodiments of the present invention can be purchased from the market, or prepared by itself using SO3 and NaF as raw materials.

[0041] The embodiments of the present application are described below in conjunction with the drawings in the embodiments of the present application.

[0042] Example 1

[0043] The electrolyte salt NaSO3F was dissolved in propylene carbonate (PC) solvent to obtain an electrolyte containing 1M NaSO3F, and 5% (volume percentage) of FEC additive was added to the electrolyte. The positive electrode was S@pPAN and the negative electrode was Na.

[0044] The preparation steps of the positive electrode material S@pPAN are as follows: weigh 8g of elemental sulfur and 1g of polyacrylonitrile into a ball mill, add anhydrous ethanol as a dispersant, and put it into a ball mill at a speed of 350r / min for 8h. Put the ball-milled slurry into an oven at 80°C to dry the ethanol. Put the dried powder into a mortar and grind it thoroughly and sieve it, then weigh a certain amount of powder into a quartz crucible and put it into a tubular furnace. In a nitrogen atmosphere, heat it to 300°C at a heating rate of 5°C / min, keep it warm for a period of time, and cool it naturally to obtain the positive electrode material S@pPAN.

[0045] Comparative Example 1

[0046] The rest is the same as Example 1, except that the electrolyte salt is NaPF6.

[0047] Comparative Example 2

[0048] The rest is the same as Example 1, except that the electrolyte salt is NaClO4, and the solvent is a mixed solvent of EC and DEC in a volume ratio of 7:3.

[0049] Figure 2 The cycle performance of the three electrolytes of Example 1, Comparative Example 1 and Comparative Example 2 at 0.1C is compared. It can be seen that the first efficiency of the NaClO4 system is the highest, which is 78%, which may be due to the presence of EC in the solvent, which can participate in film formation together with FEC. The first efficiencies of the NaPF6 and NaSO3F systems are similar, which are 76.61% and 75.38% respectively. It is speculated that they are mainly formed by the additive FEC. Compared with the blank group, the addition of 5% FEC has a significant improvement in the first efficiency. The first discharge specific capacity of the NaSO3F system is 557.3mAh / g, and the discharge capacity is still 384mAh / g after 400 cycles, and the capacity retention rate is 83.0%. The discharge specific capacity of the NaSO3F system is not as good as that of the NaPF6 system, but it is worse than the NaClO4 system. The discharge capacity of the NaClO4 system after 400 cycles is 305.2mAh / g, and the capacity retention rate is only 62.8%.

[0050] Example 2

[0051] HC is a major non-graphitized form of carbon derived from various precursors such as petroleum pitch, coal tar pitch, polymers and biomass. It has received great attention as anode materials for alkali metal ion batteries. Its high disorder provides many active sites for the storage of alkali metal ions, resulting in high capacity and good cycling stability. In addition, HC has multiple advantages, including high natural abundance of precursors, low cost, environmental friendliness, high mechanical strength and thermal stability, making it a very promising candidate for future energy storage. Therefore, HC is considered to replace Na metal for matching NaSO3F electrolyte.

[0052] Weigh hard carbon, conductive agent (Super P), and binder (CMC) in a mass ratio of 90:5:5 and grind them manually in a mortar, then transfer them to a planetary ball mill and grind them at a speed of 420r / min for 4h. After the ball milling is completed, use a film applicator to evenly coat the mixed slurry on the surface of the carbon-coated aluminum foil, put the electrode into an 80℃ vacuum oven to dry overnight, and use a slicer to punch out The discs are set aside.

[0053] Using a solvent with a ratio of EC:PC of 1:1, 1M NaSO3F and 1M NaPF6 electrolytes were prepared, and 2% of the film-forming additive FEC was added to them. Button cells were assembled and their cycling performance was tested at a rate of 0.1C. EIS tests were performed on the two batteries before cycling, and the results are shown in Figure 2. Figure 3 As shown in content (a), the interfacial impedance of the NaSO3F group is higher than that of the NaPF6 group, but the difference between the two is not large. This may be because the conductivity of the NaPF6 electrolyte is higher than that of the NaSO3F electrolyte. Figure 3 Content (b) is a comparison of the cycle performance of the two batteries. It can be seen from the figure that the NaPF6 group has better compatibility with the HC negative electrode, which is specifically reflected in the higher discharge specific capacity. For the NaSO3F group, the first charge and discharge efficiency was 85.32% when cycled at a rate of 0.1C, which is similar to the first efficiency of the NaPF6 group. The capacity retention rate of the NaSO3F group still reached more than 99% after 90 cycles, and the coulombic efficiency also reached more than 99%. However, the capacity retention rate of the NaPF6 group after 90 cycles was only 86%.

[0054] Example 3

[0055] The rest is the same as in Example 1, except that 5% FEC is replaced by 5% VC.

[0056] The effects of the two additives in Example 1 and Example 3 on the battery performance are compared. Figure 4As shown. Adding 5% (volume ratio) of the two film-forming additives FEC and VC can make the battery cycle stably within 400 cycles. The coulombic efficiency of these two groups of batteries is above 99%, but there are some differences in the discharge specific capacity. The group with VC added is lower than the FEC group at the beginning of the cycle, and gradually surpasses the group with FEC additives after 150 cycles. Later, the discharge specific capacities of the two groups gradually approached each other around 400 cycles. Figure 5 The specific capacity-voltage diagrams of the two systems at the 1st, 50th and 250th cycles are compared. The group with 5% VC added has the highest first-cycle discharge specific capacity of 599.6 mAh / g, and the capacity retention rate is 73.3% after 400 cycles.

[0057] Figure 6 The figure shows the rate performance comparison when 5% FEC and 5% VC are added to 1M NaSO3F with PC as solvent. The battery is assembled using S@pPAN electrode and Na metal negative electrode, and is cycled for 5 cycles at rates of 0.05C, 0.1C, 0.25C, 0.5C, 1C, and 3C, and then returned to the rate of 0.1C (1C = 1650 mAh / g). The corresponding relationship between the number of cycles and the discharge specific capacity is shown in the figure. The charge specific capacity of a group of batteries with FEC added at the rates of 0.05C, 0.1C, 0.25C, 0.5C, 1C, and 3C is 896.2 mAh / g, 851.4 mAh / g, 714.7 mAh / g, 444.1 mAh / g, 193.4 mAh / g, and 2.1 mAh / g, respectively, and then when the rate is restored to 0.1C, the specific capacity is restored to 885.46 mAh / g. The charge capacity of a group of batteries with VC added at the rates of 0.05C, 0.1C, 0.25C, 0.5C, 1C, and 3C were 868.6mAh / g, 853.5mAh / g, 773.2mAh / g, 635.3mAh / g, 385.0mAh / g, and 90.1mAh / g, respectively. Then, when the rate was restored to 0.1C, the specific capacity of this group was restored to 911.0mAh / g. From this data, it can be seen that the group with 5% VC additive has better performance at high rates, and still has a charge capacity of 90.1mAh / g at 3C, while the group with FEC as an additive has a larger capacity reduction at 0.5C, and basically no reversible capacity at 3C rate. However, when it is restored to a small rate, the reversible capacity of these two groups of batteries returns to normal levels.

[0058] Comparative Example 3

[0059] The rest is the same as Example 1, except that the positive electrode is replaced with sodium nickel iron manganese oxide.

[0060] Comparative Example 4

[0061] The rest is the same as Example 1, except that the positive electrode is replaced by sodium vanadium phosphate.

[0062] Comparative Example 5

[0063] The rest is the same as Example 1, except that the positive electrode is replaced by Prussian blue.

[0064] Comparative Examples 3, 4 and 5 use Na metal as the negative electrode and three common sodium-sulfur battery materials, sodium nickel iron manganese oxide / sodium vanadium phosphate / Prussian blue, as the positive electrode to assemble button batteries respectively, use 1MNaSO3F electrolyte, and the solvent is a mixed solvent of EC / PC with a volume ratio of 1:1. The battery is charged and discharged at a rate of 0.1C (1C=300mAh / g), thereby verifying the adaptability of NaSO3F electrolyte to the high-voltage positive electrode commonly used in sodium-ion batteries.

[0065] Layered oxides have a periodic layered structure, simple preparation method, high specific capacity and voltage, and are the main positive electrode materials for sodium ion batteries. Sodium nickel iron manganese oxide positive electrode is a representative of layered oxide positive electrodes. A battery with sodium nickel iron manganese oxide as the positive electrode, Na as the negative electrode, 1M NaSO3F as the electrolyte, and a rate of 0.1C (1C = 300mAh / g), Figure 7 Content (a) is the time-voltage curve of the battery charge and discharge cycle; content (b) is the capacity-voltage curve. The battery cycle is divided into three stages. The first stage is a sudden drop in voltage at the beginning of the cycle, and it takes 19 hours to charge to the specified voltage. Overcharging occurs. It is speculated that it may be caused by a soft short circuit inside the battery. The continuous growth of Na dendrites pierces the diaphragm. Another possibility is that the metal ions of the positive electrode are dissolved, reduced at the negative electrode, and continuously accumulated, causing a short circuit. Figure 7 From the content (a), we can know that the second stage is that the battery undergoes four cycles of charge and discharge, but the coulomb efficiency is very low during the cycle, indicating that the battery has generated a large amount of irreversible capacity. There are three possible reasons for the generation of irreversible capacity. One is the continuous occurrence of soft short circuits, and the electrolyte conducts electrons and ions at the same time. The second is that some irreversible reactions occur between the positive electrode and the electrolyte, which lead to an increase in capacity. In addition, the instability of the electrolyte to Na may also lead to low coulomb efficiency. The reaction activity between the electrolyte and Na is strong, and the electrolyte and solvent continue to decompose, and a stable SEI cannot be formed on the Na surface. The third stage is that after the voltage reaches the highest chargeable point, the voltage continues to drop, and then tends to a stable value, but the battery capacity continues to rise. This is a typical hard short circuit phenomenon. The battery gradually transforms from a long-term soft short circuit to a hard short circuit, and the positive and negative electrodes are in direct contact. In this process, the electrolyte is continuously consumed.

[0066] The same method was used to test the compatibility of NaSO3F electrolyte with sodium vanadium phosphate and Prussian blue positive electrodes. The two groups of positive electrodes showed the same charge and discharge results, such as Figure 8 As shown in the figure, content (a) is with sodium vanadium phosphate as the positive electrode, and content (b) is with Prussian blue as the positive electrode. The battery will drop after the first cycle is charged to about 3.1V, and then tend to a stable value. This is the same as the second half of the charge and discharge results of the battery with sodium nickel iron manganese oxide as the positive electrode.

[0067] It can be seen that when the NaSO3F electrolyte is matched with the three types of positive electrode materials, sodium vanadium phosphate, sodium nickel iron manganese oxide, and Prussian blue, the battery has a slight internal short circuit phenomenon, resulting in the battery charging voltage failing to reach the theoretical expectation and failing to discharge effectively. The analysis of the battery failure mechanism found that when the battery reaches 3V (vs. Na + / Na), the NaSO3F electrolyte will cause the transition metal ions in these three types of positive electrodes to dissolve and migrate to the negative electrode. Irreversible chemical reactions will continue to occur inside the battery, leading to irreversible capacity loss.

[0068] Example 4

[0069] The rest is the same as Example 1, except that sodium difluorooxalate borate is also introduced into the electrolyte, and the molar ratio of NaSO3F to sodium difluorooxalate borate is 1:1. With sodium vanadium phosphate as the positive electrode and sodium as the negative electrode, the charge and discharge interval is 2-4V, and the rate is 0.1C. The battery is charged and discharged. The experiment found that the battery can be charged and discharged normally, and its first cycle discharge capacity is 15mAh / g. After 100 cycles, the capacity retention rate is still 98%. It shows that if sodium difluorooxalate borate is introduced into the electrolyte, the problem that a single NaSO3F-based electrolyte cannot match a variety of positive electrode materials can be solved.

[0070] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any person skilled in the art who is familiar with the present technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A sodium ion battery electrolyte containing NaSO3F, characterized in that: The invention comprises an electrolyte salt, a solvent and an additive, wherein the electrolyte salt contains NaSO3F.

2. The electrolyte according to claim 1, characterized in that The solvent is an ester solvent.

3. The electrolyte according to claim 1, characterized in that The solvent is one or more of ethylene carbonate, propylene carbonate, dimethyl ether, diethyl carbonate and THF.

4. The electrolyte according to claim 1, characterized in that The concentration of NaSO3F in the electrolyte is 0.5-2M.

5. The electrolyte according to claim 1, characterized in that The additive is a film-forming additive, preferably fluoroethylene carbonate and / or vinylene carbonate.

6. The electrolyte according to claim 1, characterized in that The volume percentage of the additive in the electrolyte is less than or equal to 5%.

7. The electrolyte according to claim 1, characterized in that The electrolyte salt further contains sodium difluorooxalatoborate; preferably, the molar ratio of NaSO3F to sodium difluorooxalatoborate in the electrolyte salt is less than or equal to 1:

1.

8. A sodium ion battery, characterized in that: Contains the electrolyte according to any one of claims 1 to 7.

9. The sodium ion battery according to claim 8, characterized in that The electrolyte salt in the electrolyte is NaSO3F, and the sodium ion battery also includes a positive electrode and a negative electrode. The positive electrode is polyacrylonitrile-sulfur, and the negative electrode is a Na metal negative electrode or a hard carbon negative electrode.

10. The sodium ion battery according to claim 8, characterized in that The electrolyte contains NaSO3F and sodium difluorooxalatoborate at the same time; the sodium ion battery also includes a positive electrode and a negative electrode, the positive electrode is sodium vanadium phosphate, sodium nickel iron manganese oxide, Prussian blue or polyacrylonitrile-sulfur, and the negative electrode is a Na metal negative electrode or a hard carbon negative electrode.